Menstrual Problems Among College Students: Prevalence and Treatment Seeking Behaviors - Hoirun Nisa; Alkausyari Aziz (JURNAL PROTEKSI KESEHATAN, 2019)
Background: Menstrual problems are highly prevalence, especially among young adults. However, the signs and symptoms of menstrual disorders are typically disregarded. Objectives: To evaluate the prevalence of menstrual problem, especially premenstrual symptoms and menstrual syndromes, and treatment seeking behavior. Methods: This was a cross-sectional study on 261 female college students. Data were collected using a structured questionnaire. Questions were about menstrual patterns, premenstrual symptoms, menstrual syndrome, its severity and treatment seeking behavior. Information about stress was collected using a perceived stress scale questionnaire. Results: Prevalence of premenstrual symptoms was 70.1%, and that of dysmenorrhea was 93.6%. Mothers were the main source (65%) of information about reproductive heatlh. Mood-swings/irritability (88.1%) and dysmenorrhea (93.5%) were most common of premenstrual symptoms and menstrual syndrome, respectively. Half of participants experienced severe dysmenorrhea (53.2%), however medical seeking behavior during menstrual period was poor (18.8%). Participants did not seek treatment because their menstrual problems did not interfere with their daily activities (80.2%). Conclusion: Premenstrual symptoms and menstrual syndrome are highly prevalent among college students of UIN Jakarta. As mothers were the main source of information regarding reproductive health, health professionals should involve mothers in discussions about menstrual problems and how to deal with them.